How many McDonald's are there? : anti-union activity and global franchise operations - Morrell, Kevin, (SAGE Business Cases., 2020)
McDonald's in Germany in the early 1990s illustrates how global franchise operations can deliver value to customers and shareholders but at the expense of employees. A study of the fast food chain from this era raises the question: Is what one might call the "winning formula" compromised if a global franchise allows trade unions to operate in the workplace? In addition, the question of how many McDonald's stores exist depends on how McDonald's chooses to comply with employee relations climates in different countries. Researcher Tony Royle has suggested that McDonald's exploited its status as a franchise to avoid placing employees on the board, a finding disputed by McDonald's.